Factors Strengthening the Fundamental Concept of Human Relations in Islamic Financial Institutions of Indonesia - Budi Sukardi; Fachrurazi Fachrurazi; Eko Asmanto (Universitas Islam Negeri Raden Mas Said Surakarta, 2022)
This study seeks to manifest the factors in strengthening and improving the fundamental concepts of human relations in Islamic banking including motivation, concepts and perceptions of individuals, power, decision-making, communication, leadership, mentality, social environment, individual differences, and human dignity. They are scrutinized in Islamic financial institutions in Indonesia. This quantitative study employed a non-experimental approach. 38 Islamic financial institutions were involved as the representative sample. Data from the questionnaire were analyzed using factor analysis to reduce the data by summarizing several factors and renaming them as new factors. Verification using factor analysis with correlation matrix showed that the human dignity provides a significant relationship to all factors in human relations in Islam with a significance of < 0.05. All factors were found valid with the highest validity of 0.802 (human dignity). The results of the reduction factor brought up three new factors social, psychological, and leadership factors. This study proves that the essential components to strengthen and improve human relations in Islamic banking are implementing and improving social, psychological, and leadership aspects.